Pharmacotherapy for the Treatment of Gastric Antral Vascular Ectasia: A Narrative Review - Peng, Mengyuan (2021)
Gastric antral vascular ectasia (GAVE) is an uncommon clinical entity leading to recurrent gastrointestinal bleeding. There is no consensus regarding treatment of GAVE. Endoscopic therapy is the preferred treatment option, but has a fairly high recurrence rate. Surgical resection can completely resolve GAVE, but is invasive with a relatively high risk of postoperative complications. Recently, the role of pharmacotherapy for GAVE has been recognized. However, the evidence is limited to scattered case reports or small case series. This review comprehensively summarizes the efficacy and side effects of drugs commonly used for the treatment of GAVE, including octreotide, cyproheptadine, cyclophosphamide, prednisolone, estrogen-progesterone, thalidomide, bevacizumab, and tranexamic acid.